Multimedia and its relevance to education - Zeki, Akram M.; Badi, Maimona J.; Haruna, Chiroma (IIUM Press, 2015)
The use of multimedia services in education is playing a vital role in the recent advancement in educational sector. The growth in the use of multimedia in Malaysian educational sector has increased rapidly in recent years and expected to continue in the future. It is believe that using multimedia elements in teaching and learning is pleasing and motivates students to acquire knowledge.